Legal Aid in Sexual Violence Cases (Novia Widyasari Case): Bantuan Hukum pada Kasus Kekerasan Seksual (Kasus Novia Widyasari) - Bambang Pamungkas; Debby Fitriana; Devita Nur Fitriyana; Ranti Nur Azizah; Anita Carolina Rajagukguk (Universitas Negeri Semarang, 2022)
The provision of legal assistance for cases of sexual violence against women, especially in the case of Novia Widyasari, still has many obstacles and challenges in its implementation. The challenge lies in 3 (three) legal systems, namely legal culture, legal substance, and legal structure. Of the three forms of challenge, the most dominating is the third challenge, namely the legal structure, namely the quality of law enforcement. With the provision of legal assistance in the form of advocacy services based on assistance and exclusive defense of victims' rights, it is hoped that it can be a stimulus in the process of upholding justice for victims of sexual violence.